2020
DOI: 10.1136/bmj.m1175
|View full text |Cite
|
Sign up to set email alerts
|

Investing in the health of girls and women: a best buy for sustainable development

Abstract: Investing in the health of girls and women: a best buy for sustainable development Human rights, theory, evidence, and common sense all suggest that greater investment in women's health could be among the "best buys" for broader economic development and societal wellbeing, say Michelle Remme and colleagues on 4 November 2020 by guest. Protected by copyright.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 53 publications
0
21
0
Order By: Relevance
“…Improving the health of women benefits all members of our society. 33 Increasing research on the health of women has been demonstrated to produce significant returns on investment. 34 The 5-year, 2019–2023 Trans-National Institutes of Health Strategic Plan for Women's Health Research sets out an ambitious vision for a world in which the biomedical research enterprise thoroughly integrates sex and gender influences through the following five strategic goals:Advance rigorous research that is relevant to the health of women.Develop methods and leverage data sources to consider sex and gender influences that enhance research for the health of women.Enhance dissemination and implementation of evidence to improve the health of women.Promote training and careers to develop a well-trained, diverse, and robust workforce to advance science for the health of women.Improve evaluation of research that is relevant to the health of women.…”
Section: Discussionmentioning
confidence: 99%
“…Improving the health of women benefits all members of our society. 33 Increasing research on the health of women has been demonstrated to produce significant returns on investment. 34 The 5-year, 2019–2023 Trans-National Institutes of Health Strategic Plan for Women's Health Research sets out an ambitious vision for a world in which the biomedical research enterprise thoroughly integrates sex and gender influences through the following five strategic goals:Advance rigorous research that is relevant to the health of women.Develop methods and leverage data sources to consider sex and gender influences that enhance research for the health of women.Enhance dissemination and implementation of evidence to improve the health of women.Promote training and careers to develop a well-trained, diverse, and robust workforce to advance science for the health of women.Improve evaluation of research that is relevant to the health of women.…”
Section: Discussionmentioning
confidence: 99%
“…32 Interventions for improving mother's health literacy and education and integrating husband's and elder's participation could be sufficient for the short-term goals. Given the lessons learned from other countries by targeting women's empowerment and gender equality, 33 Vietnam should integrate these aspects into its national action plan to improve UHC and other health-related SDG outcomes in the long run.…”
Section: Discussionmentioning
confidence: 99%
“…While this work has brought increased visibility on the data and best practices to advance care, there is global lag in translation of findings into clinical policies and national policy. Outside of maternal child health, women's health and, importantly, gender‐based differences in health and health outcomes continue to lag 101 . In addition, it is key to address the impacts of health system infrastructure on gender‐based differences in care and subsequent health outcomes 102 .…”
Section: Recommendations To Reduce Gender Disparities In Ncdsmentioning
confidence: 99%